INFORMATION SYSTEM AUDITING USING COBIT 5 ON PRADITA UNIVERSITY E-LEARNING ASWAYA - Panduwitama, Aldira; Atmojo, Wahyu Tisno (Informatika, Universitas Jenderal Soedirman, 2024)
Learning management sytems (LMS) play a crucial role to an academic process in a modern university, LMS systems facilitate an online learning process and help teach and it students to connect. This system is considered vital by its nature to ensure a smooth academic process, that’s why keeping the sensitive data and information that are contained in it are a must and ensuring the security are top priority.Whereheas LMS that are used in Pradita University havent got its system information audited. By using COBIT 5 developed by ISACA gives a solution to align IT with the organization goals, ensure its security, manage risk and threats and also manage compliance to a current policy. The main goal of this research is to understand its IT management, Especially on Security sector and Service request incident that contained in COBIT 5 domains like DSS02, DSS04, DSS05 and how this information system compliance to external regulations that already stated by an external organization as contained in MEA03 domain. And the result of its maturity level that have been assesed on Domain DSS02 is 2 DSS04 level 3 DSS05 level 5 and MEA03 is on level 3. That makes LMS aswaya have an average of 2.5 on its maturity level and have 0,5 gap from the expected level of 3. This shown because most of the processes on LMS Aswaya are Repeatable but inituitive.